Sex-specific and regional differences in the prevalence of diagnosed autoimmune diseases in Germany, 2022 - Manas K. Akmatov; Claudia Kohring; Frank Pessler; Jakob Holstiege (Research in Health Services & Regions)
Abstract Background Research on the epidemiology of autoimmune diseases is impeded due to the rarity of most autoimmune diseases. We aimed to assess the prevalence of diagnosed autoimmune diseases in Germany and examine their sex-specific and regional differences. Methods A cross-sectional study using the nationwide ambulatory claims data of females and males of any age with statutory health insurance from 2022 was designed (N = 73,241,305). Autoimmune diseases were identified by diagnostic codes of the International Classification of Diseases and Related Health Problems, 10th Revision, German Modification (ICD-10-GM). Regional differences were examined at the level of urban and rural districts (N = 401). To control for demographic differences across districts we applied the direct standardization method to calculate sex- and age-standardized prevalences with the German population in 2022 used as a standard population. Furthermore, we calculated prevalence ratios (PR) and 99% confidence intervals (99% CI) to examine sex differences. Results Of 73,241,305 insurees (median age, 45; interquartile range, 26–63 years), 6,307,120 had at least one (any) autoimmune disease in 2022, corresponding to a crude prevalence of 8.61% (99% CI: 8.60–8.62%). Of all individuals with autoimmune diseases, 67% were females. The prevalence of single autoimmune diseases varied between 0.008% (pemphigus) and 2.3% (autoimmune thyroiditis). Other autoimmune diseases with a high prevalence were psoriasis (1.9%), rheumatoid arthritis (1.4%), and type 1 diabetes (0.75%). The prevalence was higher in females than males for 25 of the 31 autoimmune diseases with the highest PR observed for autoimmune thyroiditis (PR 5.92; 99% CI: 5.88–5.95), primary biliary cirrhosis (5.60; 5.36–5.84) and systemic lupus erythematosus (5.15; 4.97–5.36). Males were more likely to be diagnosed than females with type 1 diabetes (1.37; 1.36–1.39), ankylosing spondylitis (1.40; 1.39–1.43) and Guillain-Barré syndrome (1.31; 1.27–1.37). The only autoimmune disease without sex difference was myasthenia gravis (1.00; 0.97–1.03). At district level the age- and sex-standardized prevalence of at least one (any) autoimmune disease differed by a factor of nearly 2 between 5.91% and 11.62%. In general, the prevalence was higher in East (former GDR) than West (former FRG) Germany. Conclusion Although most autoimmune diseases were rare, when considered as a whole, autoimmune diseases turned out to be more common than previously assumed, with one out of 12 individuals affected in Germany.